2019
DOI: 10.3329/bjch.v43i1.41210
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Overweight and Obesity among Children and Adolescents in Bangladesh: A Hospital Based Study

Abstract: Background: Childhood obesity is becoming an epidemic globally as well as in Bangladesh. Although several risk factors are identified for overweight or obesity, limited studies have been done in our country. The objective of this study was to identify the risk factors of overweight and obesity in children and adolescents in Bangladesh. Methodology: It was a cross sectional study done in children, aged 5 to 16 years, attending the Paediatric Endocrine Clinic and Paediatric Outpatient Department, Bangaband… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Overnourished parents, high family income, and sedentary lifestyles were thought to be the potential risk factors for children being overweight and obese [ 34 ]. A recent study showed that watching television more than 3 hours per day, breast feeding for less than 6 months, high calorie intake, and maternal overweight increases the risk of childhood obesity in children aged 5–16 years in Bangladesh [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overnourished parents, high family income, and sedentary lifestyles were thought to be the potential risk factors for children being overweight and obese [ 34 ]. A recent study showed that watching television more than 3 hours per day, breast feeding for less than 6 months, high calorie intake, and maternal overweight increases the risk of childhood obesity in children aged 5–16 years in Bangladesh [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The obesity-related childhood behavior is not only shaped by parental behavior but also by 5 critical obesogenic environments: schools, television, the internet, retailers, and food advertising campaigns. The term "obesogenic environments" has been defined by Swinburn and colleagues as "the sum of the influences that the surroundings, opportunities or conditions of life have on promoting obesity" 37,[51][52][53] .…”
mentioning
confidence: 99%